2011
DOI: 10.3928/1081597x-20110106-03
|View full text |Cite
|
Sign up to set email alerts
|

Phakic Intraocular Lens Implantation in United States Military Warfighters: A Retrospective Analysis of Early Clinical Outcomes of the Visian ICL

Abstract: This retrospective analysis of 3-month outcomes suggests that Visian ICL implantation in myopic warfighters provides excellent refractive and visual results. Further study is needed to evaluate long-term results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…Studies reporting on Visian ICL and Visian TICL have demonstrated good efficacy and safety profiles for the correction of high ametropias in patients without keratoconus (11)(12)(13). Fewer studies have reported on Visian TICL in the correction of myopia and irregular astigmatism associated with keratoconus (8,14) and only 4 studies reported the safety and efficacy of TICL implantation after ICRS implantation without CXL treatment (15)(16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…Studies reporting on Visian ICL and Visian TICL have demonstrated good efficacy and safety profiles for the correction of high ametropias in patients without keratoconus (11)(12)(13). Fewer studies have reported on Visian TICL in the correction of myopia and irregular astigmatism associated with keratoconus (8,14) and only 4 studies reported the safety and efficacy of TICL implantation after ICRS implantation without CXL treatment (15)(16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…Another attractive aspect of this surgery is that it offers a mode of correction that is both theoretically reversible and predictable, allowing the cornea to remain essentially intact without permanent alteration. [7][8][9][10][11] Furthermore, these IOLs deliver excellent refractive results with rapid visual recovery and excellent predictability compared with other refractive procedures whose results are dependent on corneal wound healing. [12][13][14] The pIOL is an option that preserves accommodation and, if necessary, it can be used in combination with other procedures such as laser in situ keratomileusis (LASIK) to correct residual refractive errors (bioptics).…”
Section: Discussionmentioning
confidence: 96%
“…Unfortunately, previous models of AC pIOLs were withdrawn from the market in 2007 because of corneal endothelial cell loss. [2][3][4][5][6][7] The GBR/Vivarte is a 1-piece pIOL made of a hydrophilic acrylic material using a polymerization process that allows the optic to be foldable and the footplates soft, while the haptics are rigid, similar to PMMA. 18,B,C Significant and sudden late-onset (4 to 5 years) endothelial cell loss that was described in France led to explantations in 10% to 20% of cases D ; the endothelial cell loss was physiological in the first 3 or 4 postoperative years.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of SMILE surgery in correcting low myopia and myopic astigmatism had been widely recognized ( 8 12 ). In recent years, few studies have also reported that EVO-ICL demonstrated good efficacy and safety in correcting low to moderate myopia ( 13 , 14 ). This study first investigated and compared the long-term visual outcomes between EVO-ICL surgery and SMILE surgery for low myopia.…”
Section: Discussionmentioning
confidence: 99%